Public Outreach in the Drents Museum in Assen (NL) - Blue van der Zwan-Deen (EXARC Journal)
The author of this article works as a museum teacher at the educational department of the Drents Museum and is an active member of the living history group Byfrost. Part of my job as museum teacher at the Drents Museum in Assen is attending to the all the groups that visit our museum. This includes the great number of children, both elementary school and high school students, that visit our museum. A lot of children think of a museum as a boring place where there is nothing to do but look at old paintings. Many only go to the museum if their parents or teachers make them go.